The goals of manufacturing strategy, P.O.M. techniques and perceptions: A pilot study - D. R. Snaddon (South African Journal of Business Management, 1993)
Managers formulate, implement and monitor strategies to pursue their goals. Implementation is important and involves, amongst others, Production and Operations Management (P.O.M.) techniques. The purpose of this article is to study, by means of a limited sample, perceptual associations between goals of manufacturing strategy and P.O.M. techniques. An attempt is made to answer two questions in this article. The first question is which specified goals are independent of each other? The second question is which P.O.M. techniques are recommended for these independent goals? Bias and the definition of P.O.M. techniques create difficulties but pilot research indicates that some specified goals are perceived as independent. More investigation is required to verify this. Some techniques are identified with specific goals and this work should be expanded.
Keywords: 650